Aplikasi Nanopartikel Perak dari Ekstrak Tumbuhan Sebagai Agen Antibakteri dalam Sediaan Gel dan Krim Wajah: Systematic Review - Syifa Nabilah Az-zahra; Pingkan Adinda Regita Putri; Ganjar Eko Prasetyo; Budiman Anwar (Khazanah Multidisiplin, 2026)
Green-synthesized silver nanoparticles (AgNPs) have emerged as promising antibacterial agents due to their high antimicrobial efficacy, good biocompatibility, and environmentally friendly synthesis process. This study aimed to analyze recent advances in the application of green-synthesized AgNPs incorporated into topical gel and cream formulations as antibacterial agents. A systematic review approach was employed by systematically searching the Scopus, ScienceDirect, PubMed, SpringerLink, and Google Scholar databases for English-language articles published between 2015 and 2025. The literature search was conducted from September 17 to October 22, 2025, using Boolean operators with the following keywords: ("silver nanoparticles" OR AgNPs) AND ("green synthesis" OR "plant-mediated synthesis") AND (gel OR cream OR "topical formulation") AND (antibacterial OR antimicrobial). The literature selection process was adapted from the PRISMA 2020 guidelines. Of the 48 identified articles, 12 met the inclusion criteria and were included in the final analysis. The findings indicate that green-synthesized AgNPs formulated in topical gels and creams exhibit significant antibacterial activity against both Gram-positive and Gram-negative bacteria. Their antibacterial performance is influenced by the type of plant extract, synthesis conditions, nanoparticle characteristics, and formulation composition. This review provides a comprehensive overview of the relationship between green synthesis methods, AgNP characteristics, and the antibacterial performance of topical formulations, offering valuable scientific insights for the development of more effective antibacterial delivery systems.